Arthroscopic Treatment of Shoulder Stiffness With Rotator Cuff Repair Yields Similar Outcomes to Isolated Rotator Cuff Repair - Parker L. Brush, M.D; Adrian Santana, B.S; Ruchir Nanavati, B.S; Gregory R. Toci, M.D; Tariq Z. Issa, B.A; Daniel J. Fletcher, M.D; Joshua Hornstein, M.D (Elsevier, 2023)
Purpose: To compare patient-reported and surgical outcome measures in patients with and without secondary shoulder stiffness (SSS) undergoing rotator cuff repair (RCR). Methods: Patients undergoing rotator cuff repair from 2014 to 2020 with complete patient-reported outcome measures (PROMs) by the short-form 12 survey (SF-12) were retrospectively reviewed to identify if operative intervention for SSS was performed alongside the RCR. Those patients with operative intervention for SSS were propensity matched to a group without prior intervention for stiffness by age, sex, laterality, body mass index, diabetes mellitus status, and the presence of a thyroid disorder. The groups were compared by rotator cuff tear (RCT) size, surgical outcomes, further surgical intervention, rotator cuff retear rate, postoperative range of motion (ROM), and SF-12 results at 1 year after surgery. Delta values were calculated for component scores of the SF-12 and ROM values by subtracting the preoperative result from the postoperative result. Results: A total of 89 patients with SSS were compared to 156 patients in the control group at final analysis. The patients in the SSS group experienced a significant improvement in the delta mental health component score (MCS-12) of the SF-12 survey that was not seen in the control group (P = .005 to P = .539). Both groups experienced significant improvement by the delta physical health component score (PCS-12) of the SF-12 survey (SSS: 7.68; P < .001; control: 6.95; P < .001). The SSS group also experienced greater improvement of their forward flexion (25.8° vs 12.9°; P = .005) and external rotation (7.13° vs 1.65°; P = .031) ROM than the control group. Conclusions: Operative intervention of SSS at the time of RCR has equivalent postoperative SF-12 survey outcome scores when compared to patients undergoing RCR without preoperative stiffness despite those patients having lower preoperative scores. Level of Evidence: Level III retrospective comparative study.